PENGEMBANGAN STRATEGI PEMASARAN UMKM GORENGAN EKA - Margarani, Selvira Shinta; Sari, Chandra Abriani Dewita; Damayanti, Damayanti (STIE Pelita Nusantara, 2025)
Micro enterprises are unformal businesses that have very small assets, capital and turnover. Another characteristic is that the type of business conditions that are carried out often change, the location of the business is sometimes less fixed, generally not served by banks, and many do not have business legality. One of the small and medium enterprises or commonly known as MSMEs that has the potential to be developed and can create jobs for rural communities in Rembang District is the “Gorengan Eka” MSME. “Gorengan Eka” is an MSME that produces various types of fried foods such as martabak, mindoan, cireng and others. In the pre-survey activities carried out by the community service team, MSME “Gorengan Eka” has weaknesses faced in developing its business, namely not having social media as information media, marketing media, affordable and limited marketing networks, less strategic place. Based on the problems obtained, the community service team made a program, namely making social media as a marketing medium for MSMEs, making business banners, and making media directions where MSMEs are located. Through this activity program, it is hoped that MSMEs will be able to compete, increase sales, increase MSME income and the welfare of MSME owners.Keyword: Strategic Marketing, Development, MSMEs